Administering analgesia sublingually is a suitable option for children with acute abdominal pain in the emergency department. - Cozzi, Giorgio; Zanchi, Chiara; Chiaretti, Antonio; Tipo, Vincenzo; Cernich, Marta; D'Anna, Carolina; Fantacci, Claudia; Conversano, Ester; Zanon, Davide; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2019)
AIM: Acute abdominal pain is a frequent complaint in children attending emergency departments. The aim of this study was to investigate the pain score reductions when children with acute abdominal pain received medication sublingually. METHODS: We carried out a multicentre randomised controlled trial in three children's hospitals in Italy between March 2015 and June 2017. Children from four to 18 years of age with acute abdominal pain were recruited if their self-reported pain was at least six on a scale from 0-10. The children were randomised to receive ketorolac 0.5 mg/kg (n = 70) or tramadol 2 mg/kg (n = 70) sublingually or a melt in the mouth powder of 20 mg/kg paracetamol (n = 70). The main study outcome was the pain scores for the three drugs after two hours. RESULTS: The 210 children (58.6% girls) had a median age of 12 years with an interquartile range of 9-14.3. The median pain scores at two hours were not significantly different between ketorolac 2.0 (interquartile ranges, IQR 0.0-4.3) and tramadol 3.0 (IQR 1.0-5.0) vs paracetamol 3.0 (IQR 0.8-5.0). The median pain reductions were all 5.0 points. CONCLUSION: Delivering analgesia sublingually was a suitable option for pain relief in children with acute abdominal pain in the emergency department.

Comparison of propofol versus propofol-ketamine combination in pediatric oncologic procedures performed by non-anesthesiologists. - Chiaretti, Antonio; Ruggiero, Antonio; Barbi, Egidio; Pierri, Filomena; Maurizi, Palma; Fantacci, Claudia; Bersani, Giulia; Riccardi, Riccardo (Pediatr Blood Cancer, 2011)
BACKGROUND: Limited data are available on the best option (short acting sedatives, opioids, or ketamine) in oncologic procedural sedation performed by non-anesthesiologists. The aim of the present prospective study is to compare the safety and efficacy of propofol-ketamine versus propofol alone, managed by trained pediatricians, in children with cancer undergoing painful procedures. PROCEDURES: Data on 121 children with acute lymphatic leukemia (ALL) undergoing procedural sedations (lumbar punctures and bone marrow aspirations) were prospectively collected and included drug doses, side effects, pain assessment, and sedation degree. Children were randomly assigned to one of the two groups: P (n = 62) receiving propofol alone and K (n = 59) in whom a ketamine-propofol combination was used. RESULTS: In group K, the total dose of propofol required was significantly lower than in group P (3.9 ± 3.6 mg/kg vs. 5.1 ± 3.6 mg/kg; P < 0.001). The incidence of hypotension was also significantly lower (11% vs. 39%; P < 0.001). Major O(2) desaturations (defined as SatO(2) < 88%) occurred principally in group P (7 vs. 1; P = 0.05). Both best analgesia and shorter recovery time were obtained with the propofol-ketamine association. No differences were observed in the degree of sedation and in the awakening quality score between the two groups. CONCLUSIONS: The combination of propofol and ketamine produced statistically significant clinical advantages combined with a higher profile of safety in children with cancer undergoing painful procedures.
Keywords: Biopsy, Needle; Bone Marrow Examination; Child; Conscious Sedation; Female; Humans; Hypnotics and Sedatives; Ketamine; Male; Neoplasms; Pediatrics; Physicians; Propofol; Spinal Puncture